Determination of one-dimensional spherically aberrated point spread function in depth profiling by confocal Raman microscopy - Miguel, María de la Paz (2012)
We present a simple experiment that allows the complete and direct characterization of the point spread function (PSF) in refraction-aberrated depth profiling experiments with confocal Raman microscopy. We used a wedge-shaped solid polymer film to induce refraction aberrations on the response of an infinitesimally thin Raman scatterer, represented by a polished silicon wafer. The system, with the film pasted on top of the Si wafer, was probed by a depth slicing technique under a dry-optics configuration. Post-acquisition processing of the Si and polymer intensity maps allowed the reconstruction of the axial PSF spatially resolved each 1 μm or less in the z-axis and for virtually continuous values of focusing depth. In agreement with theory, we found that PSF broadens asymmetrically with focusing depth, with a marked shift in the focus point. From the shape of PSF, we obtained values of depth resolution within the film that confirm that axial discrimination is not drastically deteriorated, as suggested by previous works, and that confocal aperture effectively reduces the collection volume even under severe refraction interference.